EVALUATING MATHEMATICS LEARNING EXPERIENCE OF GRADE 7 STUDENTS OF BATO SCHOOL OF FISHERIES - Leomarich F. Casinillo; Rechin S. Galenzoga; Darwin L. Raagas (Sanata Dharma University Yogyakarta, 2020)
A positive learning experience stems from active engagement with the lesson and greater interaction in learning activities. This study investigated the types of learning experience of students in Bato School of Fisheries, Leyte, Philippines such as Hands-on, Minds-on and Authentic Learning. Also, the study analyzed the students’ level of achievement in learning mathematics under each type of learning experience. The study employed a random of 25% of the grade 7 students for experimental design that involves qualitative and quantitative approach. Result shows that the Hands-on learning experience of students is in beginning level which needs a proper guidance of the mathematics teacher. It is shown that students are more capable of Hands-on group activities in mathematics. For Minds-on learning experience, students are also in beginning level, however, it is found out that they are good in critical thinking processes which create and recreate mathematics concepts for the core topics. Furthermore, authentic learning experience is in beginning level, lowest among the 3 types of learning experience. This means that students must develop their problem solving skills in mathematics with the aid of suitable teaching strategies. Anyhow, it is found out that these students have a proficient level in mathematics achievement probably by their past knowledge. Hence, a good level of achievement in mathematics can be maintain or improve through enhancing the 3 types of learning experience especially the authentic aspect.